A Sensitive Spectrophotometric Estimation of Nimodipine in Tablets and Injection Using Phloroglucinol. (22nd May 2013) - Deepakumari, Hemavathi N.; Revanasiddappa, Hosakere D.
Abstract : A rapid, simple, and sensitive spectrophotometric method has been described for the determination of nimodipine in bulk drug, tablets, and injection. The proposed method is based on the diazotization of reduced nimodipine with nitrous acid followed by coupling with phloroglucinol to form colored azo dye and showing absorption maximum (λ max ) at 410 nm. The formed colored azo dye is stable for about more than 2 h. The method obeyed Beer's law over the concentration range of 0–25  μ g/mL and the corresponding molar absorptivity value is 1.23 × 10 4  L/moL/cm. The Sandell sensitivity values limits of detection (LOD) and quantification (LOQ) values have also been reported for the developed method. The accuracy and precision of the method was evaluated on intra- and interday basis; the relative error (%RE) and the relative standard deviation (RSD) were <2.0%. All variables have been optimized and the presented reaction sequence was applied to the analysis of nimodipine in bulk drug, tablets, and injections. The performance of this method was evaluated in terms of Student's t -test and variance ratio F -test to find out the significance of proposed method over the reference method.